How is the Oral Hygiene of Elementary School Students?- Saliva pH, Saliva Volume and Saliva Viscosity - A’yun, Quroti (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: Salivary pH, saliva volume, and saliva viscosity as part of the host affect the health of the oral cavity. High saliva viscosity affects the decrease in salivary flow rate which causes the accumulation of food debris which can eventually lead to plaque and tartar. Objective: This study aims to determine the effect of saliva status on the OHI-S index in elementary school children. Methods: This type of research is observational with a cross-sectional design. The study was conducted on elementary school students in four elementary schools in Sleman City, Yogyakarta, with a total sample of 100 children. The independent variable is salivary status and the dependent variable is the OHI-S index. Collecting data by examining salivary status and examining OHI-S and analyzing data using Chi-Square. Result: there is an effect between pH, volume, and viscosity of saliva on the OHI-S index in children aged 9-11 years with p<0.05. Conclusion: saliva status affects the oral hygiene of elementary school students.